(untitled) (Research, Society and Development, 2023)
The electronic cigarette is a nicotine delivery device that appears as an alternative to the traditional cigarette. As for its epidemiology, the incidence is higher among young males aged 15 to 24 years, especially those who are still in the school environment. Thus, prolonged use of this electronic system can cause periodontitis, which is a multifactorial disease aggravated by smoking, since salivary nicotine levels alter the oral microbiota and gingival blood flow, decreasing the immune response. Therefore, this study aimed to make a bibliographic survey on the correlation between the use of electronic cigarettes and the development of periodontitis in young people. As for the methodology used, it consists of a narrative literature review, through searches in the Google Scholar, Scopus, PubMed, MEDLINE and LILACS databases via VHL in the period from 2013 to 2022. Through this, it was found that the causes that lead young people to use these devices are, above all, social and that the vapor of the electronic cigarette is an aggravating factor for the formation of periodontitis in young people due to the changes caused at the cellular level. However, the population still does not have total knowledge of the clinical findings that prove this relationship, making it difficult to raise awareness, and therefore, to minimize this habit. In view of this, the dental surgeon has the role of preventing the evolution of periodontitis by warning about the risks of continuing to use electronic cigarettes.